Controlled release of Montelukast Sodium from pH-sensitive injectable hydrogels. Issue 9 (13th June 2019) - Javeria, Irtaza; Islam, Atif; Gull, Nafisa; Ghaffar, Abdul; Khan, Shahzad Maqsood; Sabir, Aneela; Khaliq, Shaista; Butt, Muhammad Taqi Zahid; Atta, Sadia
ABSTRACT: pH sensitive hydrogels showed excellent drug release properties, with promise for other biomedical applications. Also, the impact of molecular weight (MW) and degree of deacetylation (DDA) of chitosan on the fabricated chitosan/poly (vinyl alcohol) (3:1 mol ratio) hydrogel with selective silane crosslinker amount was evaluated for controlled drug delivery. The FTIR spectroscopy confirmed the incorporated components and the developed interactions among the polymer chains. The hydrogel characteristics were expressed by their responsive behaviour in different environments (water, ionic media and pH). The hydrogel sample (CH1000) having chitosan with higher MW and DDA exhibited more thermal stability and bacterial growth inhibition against E.coli . All hydrogels exhibited maximum swelling at basic and neutral pH and less swelling was observed in acidic media. For drug release analysis performed in simulated gastric fluid, hydrogel showed controlled drug release in 2 h but it was more than 10%, consequently cannot be used for oral purpose. In simulated intestinal fluid, hydrogels exhibited more than 80% release within 90 min. This characteristic phenomenon at neutral pH empowered hydrogel appropriate towards injectable and targeted controlled release of applicable drug. It was concluded that the prepared hydrogel can be administered directly into the venous circulation through syringe and can be used with better results for biomedical applications. Graphical Abstract: